The Influence of the Provo Movement and the New Culture Movement on the Surrealist Phenomenon of the Orange Alternative - Moldovan-Cywinska, Marta (Cultural Arts Research and Development, 2025)
This text will contribute to research into the phenomenon of the Orange Alternative protest-artist movement, which the author examines not only as a researcher but also as a “witness to history” (students, young researchers who, due to their age, position, or social involvement, observed important or interesting events—a term used by historians in Poland). The author talks about selected cultural and literary contexts and presents the facts—including those that are less known—about the activities of the Dutch Provo movement and the Polish New Culture Movement (and thus an exemplification of the Western European and indigenously Polish influences) on the formation of the Orange Alternative movement, taking into account its specific European and Polish features, as an artistic, political and literary phenomenon in the spirit of the ‘new surrealism’, The Orange Alternative combined joy the idea of street happenings organized in a joyful atmosphere and contestation, written forms of contesting authority in Poland in the form of manifestos. The Dutch Provo movement and the New Culture Movement had a significant influence on the Orange Alternative, particularly on its program texts and happenings. Without them, the phenomenon of Polish surrealism would not have taken shape. The author proposes an analytical method with elements of comparative studies focusing on selected happenings and texts. She will analyse selected happenings and aspects of the most important programme text as an example of the activities of the Orange Alternative, inspired by the Dutch Provo movement and the Polish New Culture Movement.